In Vivo Subcellular Mass Spectrometry Enables Proteo‐Metabolomic Single‐Cell Systems Biology in a Chordate Embryo Developing to a Normally Behaving Tadpole (X. laevis). Issue 23 (8th April 2021) - Lombard‐Banek, Camille; Li, Jie; Portero, Erika P.; Onjiko, Rosemary M.; Singer, Chase D.; Plotnick, David O.; Al Shabeeb, Reem Q.; Nemes, Peter
Abstract: We report the development of in vivo subcellular high‐resolution mass spectrometry (HRMS) for proteo‐metabolomic molecular systems biology in complex tissues. With light microscopy, we identified the left‐dorsal and left‐ventral animal cells in cleavage‐stage non‐sentient Xenopus laevis embryos. Using precision‐translated fabricated microcapillaries, the subcellular content of each cell was double‐probed, each time swiftly (<5 s/event) aspirating <5 % of cell volume (≈10 nL). The proteins and metabolites were analyzed by home‐built ultrasensitive capillary electrophoresis electrospray ionization employing orbitrap or time‐of‐flight HRMS. Label‐free detection of ≈150 metabolites (57 identified) and 738 proteins found proteo‐metabolomic networks with differential quantitative activities between the cell types. With spatially and temporally scalable sampling, the technology preserved the integrity of the analyzed cells, the neighboring cells, and the embryo. 95 % of the analyzed embryos developed into sentient tadpoles that were indistinguishable from their wild‐type siblings based on anatomy and visual function in a background color preference assay. Abstract : Single‐cell mass spectrometry was advanced to enable dual characterization of proteins and metabolites in identified cells in Xenopus laevis embryos. The analyzed embryos developed to normally behaving tadpoles with anatomy and visual function indistinguishable from that of their control siblings in a background color preference assay. In vivo single‐cell mass spectrometry expands the analytical toolbox of molecular systems, cell, and developmental biology.